2012
DOI: 10.2749/101686612x13216060213437
|View full text |Cite
|
Sign up to set email alerts
|

Causes and Consequences of Metallic Bridge Failures

Abstract: Robustness evaluation of bridges within a risk-based framework requires estimation of the probability of occurrence of different hazards followed by an assessment of the vulnerability of the bridge with respect to those hazards, as well as quantification of the consequences of potential failure. The first part of the paper deals with a statistical analysis of past metallic bridge failures which can aid towards identifying the principal hazards affecting the bridges and their associated vulnerability. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(35 citation statements)
references
References 4 publications
1
32
0
2
Order By: Relevance
“…The failure consequences C f can be estimated on the basis of the total annual risk R. Since the main reason for the existence of civil infrastructures is public interest, failure consequences need to include all social losses such as (more examples in [1] For consistency, all the costs need to be expressed on a common basis. Costs of the measure are normally specified in a present value.…”
Section: Principles Of Risk Optimisationmentioning
confidence: 99%
See 1 more Smart Citation
“…The failure consequences C f can be estimated on the basis of the total annual risk R. Since the main reason for the existence of civil infrastructures is public interest, failure consequences need to include all social losses such as (more examples in [1] For consistency, all the costs need to be expressed on a common basis. Costs of the measure are normally specified in a present value.…”
Section: Principles Of Risk Optimisationmentioning
confidence: 99%
“…Even smaller disruptions due to traffic restrictions or failure of some elements of the network may result in high consequences and negative environmental impacts [1]. In such a case the network and its major components are classified as a "critical infrastructure (object)" that can be defined as (see the European Directive 2008/114/EC [2]): an asset, system or part thereof which is essential for the maintenance of vital societal functions, health, safety, security, economic or social well-being of people, and the disruption or destruction of which would have a significant impact in a state as a result of the failure to maintain those functions.…”
Section: Introductionmentioning
confidence: 99%
“…A broad overview of the various bridge failure consequences is presented in Imam and Chryssanthopoulos (2012), and this short discussion is based on their work, while more emphasis is placed here on these aspects that are of particular importance or are more specific to seismic failure consequences. It must be made clear at the onset of any consideration of bridge failure consequences that their modelling is multifaceted, complex and inherently uncertain.…”
Section: Bridge Seismic Risk Modelling: Consequences Of Bridge Failurementioning
confidence: 99%
“…In the case of metallic bridges, the former manifests itself through fatigue, 99 whereas the latter is principally related to propensity to corrosion; either can have major 100 implications on safety, functionality and appearance. This study focuses on corrosion, which 101 is a commonly observed cause of damage and failure in metallic bridges (Wardhana & 102 Hadipriono, 2003, Imam & Chryssanthopoulos, 2012). 103…”
Section: Introduction 76mentioning
confidence: 99%